Analisa Kekerasan dan Keausan Cylinder Sleeve dari Besi Cor Kelabu FC250 Hasil Sand Mold Casting - Sumpena Sumpena; Hb. Sukarjo; Wardoyo Wardoyo; Soksono Singgih Pramana (Jurnal Engine: Energi, Manufaktur, dan Material, 2021)
The Cylinder sleeve is an engine component that is mounted on the cylinder block which functions as a piston glide base. The cylinder sleeve is made of FC250 gray cast iron. FC250 is a gray cast iron that has lamellar graphite with a tensile strength of at least 250 MPa. This study aims to determine the mechanical properties of hardness and wear of the Cylinder Sleeve made of gray cast iron FC250. The method used in this research is gray cast iron which is cut with a length of 5.5cm, thickness 0.7cm, height 0.7cm which is formed according to the standard size of the hardness and wear test. The tests carried out include testing brinell hardness and wear. The results showed that the lowest hardness value was 134.63BHN and the highest hardness value was 191.43BHN. The increase in hardness values is influenced by the carbon content that cannot be spread evenly, which is followed by a fast cooling rate. The results of the wear test obtained the lowest price of 0.00017mm³/kg.m and the highest wear price of 0.00028 mm³/kg.m.